A community pharmacist home visit project for high utilizers under a universal health system: A preliminary assessment. Issue 4 (April 2019) - Huang, Yu-Ying; Cheng, Shou-Hsia
Highlights: The community pharmacist home visit project successfully activated the managerial role of community pharmacists. The community pharmacist home visit project significantly reduced the number of physician visits among enrollees. The community pharmacist home visit project led to better medication management and modest medical expense reduction. Health authorities must develop programs to increase patient engagement in home-based disease management. Abstract: Due to the increasing prevalence of multimorbidity, the percentage of heavy users of health care services increased rapidly. To contain inappropriate outpatient visits and improve better medication management of high utilizers, the National Health Insurance Administration in Taiwan launched a community pharmacist home visit (CPHV) project for high utilizers in 2010. We employed a natural experimental design to evaluate the preliminary effects of the CPHV project. The intervention group consisted of patients enrolled in the CPHV project during 2010 and 2013. Patients in the comparison group were non-enrollees selected via a propensity score matching technique. A difference-in-differences analysis was conducted by using multilevel models to examine the effects of the project. The average number of physician visits decreased from 130.0 to 98.9 visits (23.8%) among the CPHV project enrollees, while the average number decreased from 99.5 to 89.5 visits (10.1%) among the non-enrollees, with a net effect of a 21.0-visit reduction. The CPHV project also led to modest reductions in the number of medication items used per day, the probability of hospital admission and yearly healthcare expenses. The CPHV project seems promising for decreasing health care utilization and costs of the patients with high-needs.